A Rapid Detection System Based on LabVIEW and Microcomputer - Ding Jianjun; Sun Chao; Wang Jun; Shao Jiayan; Liu Yanqun (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Excessive inhalation of formaldehyde is harmful to health. A quickly digital detection model of the content of formaldehyde in the air is designed in this paper. It can change nanoamps current into proper Voltage for TLC1543 through MAX407 and OP37.And a hardware circuit is designed for adaption and acquisition of the data. The method of this system is sending the signal to the host computer through a serial port and then showing the content of formaldehyde on the PC. Such digital detection of formaldehyde can be used to judge whether the content of formaldehyde is over the sustaining level of human body in a intuitive and quickly way. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2615